Sri Lanka : Country Procurement Assessment Report, Volume 1. Main Report - World Bank (Washington, DC, 2013)
This country procurement assessment report (CPAR) is presented in two volumes: Volume I is the Summary Report and Volume II is the Detailed Report. Volume I describes the key findings on the effectiveness and transparency of the present Public Procurement System and includes a recommended action plan for improving the system. Vol. II presents the in-depth study of the existing Financial Regulations, Guidelines and the legal system in relation to procurement (in the absence of a Public Procurement Law), procedures followed for Government-funded programs vis-à-vis those funded with external assistance, standardization of documents, and the organizational setup for procurement processing and implementation, together with a General Risk Assessment. The CPAR is based on the responses to the questionnaires received, documents reviewed and interviews held. The team sent out three sets of questionnaires: one for selected government ministries, a second for the selected implementing agencies which had major procurements, and a third for the contractors' association; and reviewed their responses.